If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 6x = -1x + 10 Reorder the terms: 10 + 6x = 10 + -1x Add '-10' to each side of the equation. 10 + -10 + 6x = 10 + -10 + -1x Combine like terms: 10 + -10 = 0 0 + 6x = 10 + -10 + -1x 6x = 10 + -10 + -1x Combine like terms: 10 + -10 = 0 6x = 0 + -1x 6x = -1x Solving 6x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6x + x = -1x + x Combine like terms: 6x + x = 7x 7x = -1x + x Combine like terms: -1x + x = 0 7x = 0 Divide each side by '7'. x = 0 Simplifying x = 0
| 2x+37=6x-7 | | 2x+1=-4 | | 2x+5=5x-16 | | 9p^2r-73pr-70r=0 | | -.75x=-6 | | r+19=27 | | 4a+8b+11a-10b= | | 5x-1-4x=1x+7 | | 3(7x+6y)=6x | | 3+6x=x-7 | | 2(x+3)+4x=6x+6 | | 6y=8+-9+6y | | 23=11+n | | 4x-6(2x+8)= | | n+2.4=-6.5 | | 0.5(2x-2)=5x+4 | | 4x+7y=71 | | x^2=8100 | | 4x-3x-5=x | | 0.04n=7.2 | | 5(-3x-3)=120 | | 79-2x=16x+15 | | ln*(x-22)=39 | | -2(4y+6)= | | 2x+1=4+4x-3 | | 3.15=15y | | 3=-3n-(-5n+1) | | 2+8x=4(2x+2)-6 | | -4k=9k | | -5h=-32/3 | | 16x^2-88x+121=0 | | -1x+4=7x-3 |